No Control - and Other Erotic Short Stories from Cupido - Cupido, (Saga Egmont, 2023)
Surrender to seduction and delve into a provocative world of desire and submission with 'No Control - and Other Erotic Short Stories from Cupido'.A curated collection of sexy story compilations which explores the pleasure of losing control and being dominated, it will leave you craving for more.This collection includes compilations such as 'Law's Lengthy... ', 'No Control', 'Fuckbitch', 'The Countess', 'Silky Dreams', 'The Boy with the Motorbike', and many more!